Assessment of three different gadolinium-based regenerators in a rotary-type magnetic refrigerator. (5th May 2019) - Li, Zhenxing; Shen, Jun; Li, Ke; Gao, Xinqiang; Guo, Xiaohui; Dai, Wei
Highlights: A compact rotary-type device for active magnetic regenerators (AMRs) has been built. Three gadolinium geometries have been studied including parallel-plates, spheres and flakes. AMRs filled with spheres/flakes provided the better cooling performance. A maximum no-load temperature span of 14.8 K was obtained at hot end temperature 300.6 K. Abstract: Room-temperature magnetic refrigeration is a recently developed, environment-friendly refrigeration technology. A rotary-type magnetic refrigerator has been built with a modified double Halbach permanent magnet array, which can provide an average magnetic field varying from 0.04 T to 1.50 T at a length of 100 mm. To evaluate the performance of AMRs with geometries, active magnetic regenerators (AMR) filled with gadolinium plates, spheres and flakes were respectively tested and compared. System performance such as temperature span, cooling power and pressure drop were investigated at different utilization factors and operating frequencies. The results revealed three AMRs performed quite differently. With larger specific heat transfer areas and smaller hydraulic diameters, AMRs filled with flakes/spheres provided better cooling performance. A maximum no-load temperature span of 14.8 K was obtained by flake-AMR with largest specific heat transfer areas and least filled mass. Sphere-AMR achieved a maximum temperature span of 10.8 K at a cooling power of 10 W among AMRs. With the same porosity and filled mass, sphere-AMR performed much better than plate-AMR, although the latter had a smaller pressure drop and associated pumping work.